2014
DOI: 10.1097/prs.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implant-Based Breast Reconstruction following Total Skin-Sparing Mastectomy in Women with a History of Augmentation Mammaplasty

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Prior radiation therapy has been studied as a risk factor for skin and wound complications after mastectomy 9,17,19,33,34 , and is underrepresented in our study population, with only 7% of patients having prior radiation. We also have no specific data on traction injury, though flap length, incision size, and time to specimen removal may be surrogates of this.…”
Section: Discussionmentioning
confidence: 99%
“…Prior radiation therapy has been studied as a risk factor for skin and wound complications after mastectomy 9,17,19,33,34 , and is underrepresented in our study population, with only 7% of patients having prior radiation. We also have no specific data on traction injury, though flap length, incision size, and time to specimen removal may be surrogates of this.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that immediate tissue expander/implant reconstructions are an acceptable option for patients requiring PMRT. More recently Sbitany et al in evaluating the morbidity associated with immediate implant reconstruction in 580 patients undergoing nipple-sparing mastectomy with or without radiation found significantly higher infections (21.6% vs 13.1%) and expander/implant losses (18.75% vs 5.1%) in radiated patients 10 . They concluded that immediate implant reconstruction in the setting of pre- or post-mastectomy radiation is a safe operation.…”
Section: Discussionmentioning
confidence: 99%
“…Hirsch et al similarly reported a 50% complication rate in patients who undergo reconstruction after PMRT 5 . In spite of these findings, multiple studies in recent years have endorsed favorable outcomes of implant reconstruction of the radiated breast and this suggests that there may be a growing acceptance of this reconstructive approach 8–10 . Implant reconstructions do provide distinct advantages including shorter operative times, less technically demanding operations, the avoidance of donor sites and potential for a shorter recovery relative to flap alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, postoperative XRT had a negative effect on satisfaction with breasts and sexual well being (Table 6 ), a finding that supports prior BREAST-Q analyses by Ho et al 21 and McCarthy et al 23 This decrease in sexual well being may ultimately be linked to poor satisfaction with their breast cosmesis, as XRT causes chest-wall distortion and capsular contractures that can introduce asymmetry and compromise aesthetics. 42 …”
Section: Discussionmentioning
confidence: 99%